The excitator as a minimal model for the coordination dynamics of discrete and rhythmic movement generation - Jirsa, V. K.; Kelso, J. A. S. (Journal of Motor Behavior, 2005)
The authors identify a class of excitable two-dimensional model systems, the excitators, that provide an entry point to the understanding of the mechanisms of discrete and rhythmic movement generation and a variety of related phenomena, such as false starts and the geometry of phase space trajectories. The starting point of their analysis is the topological properties of the phase flow. In particular, the phenomenon of false starts provides a characteristic structural condition for the phase flow, the separatrix, which partitions the phase space. Threshold phenomena, which are characteristic of excitable systems, as well as stable and unstable fixed points and periodic orbits, are discussed. Stable manifolds in the proximity of fixed points, resulting in an overshoot and a slow return phase after movement execution, are predicted in the analysis. To investigate coordination phenomena, the authors discuss the effects of two types of couplings, the sigmoidal coupling and a truncated version thereof, known as the Haken-Kelso-Bunz (HKB) coupling. They show analytically and numerically that the sigmoidal coupling leads to convergence phenomena in phase space, whereas the HKB coupling displays convergent as well as divergent behaviors. The authors suggest a specific representation of the excitator that allows the quantification of the predictions.